How much genetic variation is stored in the seed bank? A study of Atriplex tatarica (Chenopodiaceae) - Mandák, B; Bímová, K; Mahelka, V; Placková, I (Molecular ecology, 2006)
We investigated to what extent the soil seed bank differed genetically and spatially in comparison to three consecutive life history stages (seedlings, mature plants, and fruiting plants) in a natural population of Atriplex tatarica. Representatives of particular life history stages from twenty subunits within a large population were randomly collected and subjected to allozyme analysis. Comparison of population polymorphism among various life history stages showed significant differences in observed heterozygosity (H(O)) and F statistics (F(IS) and F(ST)), but nonsignificant ones in the cases of number of alleles per polymorphic locus (A) and gene diversity (H(S)). These results indicate an increasing number of heterozygotes, a decreasing level of inbreeding and an increase of the partitioning genetic diversity among populations with increasing population age. Spatial autocorrelation was used to calculate f, the average co-ancestry coefficient between individuals within distance intervals of two meters along a 39 m long transect. Significant positive fine scale genetic structure was detected in mature and fruiting plants but not in soil seeds and seedlings stages. The results of the presented study on A. tatarica indicated that significant differences exist in genetic differentiation, differentiation in allele frequencies and spatial autocorrelation among early (soil seeds and seedlings) and late (mature and fruiting plants) life history stages but not within early and late ones. This pattern suggests that, rather than storing genetic variability in the soil or germination and establishment success, self-thinning might be the major microselective force in populations of A. tatarica.
Keywords: Alleles; Soil; alely; půda; genetická variace; Atriplex; semena rostlinná; Genetic Variation; Heterozygote; heterozygot; Seeds